Experimental Study on Fire and Explosion Characteristics of Power Lithium Batteries with Surfactant Water Mist. (2018) - Zhu, Ming-xing; Zhu, Shun-bing; Gong, Jun-hui; Zhou, Zheng
Abstract: In order to improve the fire resistance of lithium battery and to study the effect of water mist containing surfactant on gas explosion in lithium battery fire, a fire extinguishing test system and an explosion test system were used to evaluate the fire extinguishing efficiency and the anti-blast performance of the lithium battery. The fire extinguishing tests show that the fire extinction time is greatly shortened after adding a certain proportion of the surface active agent to the pure water. The active agent could rapidly reduce the temperature of the combustion, wet and penetrate the surface of the combustibles and finally achieve rapid and safe fire extinguishing effect. The experimental results show that the addition of surfactant water mist reduces the temperature generated during the explosion in a short time, slows down the explosion flame propagation speed and weakens the intensity of the explosion. Through the analysis of the results of fire and explosion suppression, it is shown that the fire can be efficiently extinguished and the explosion can be significantly suppressed by adding no more than 5% surfactant.